Delayed Presentation of Morphine-Induced Respiratory Depression: A Case Report - Islam Mukhtar; Omar Mudawi; Abdulrahman H. Alashkar; Raed Ali Abuajamieh (Dr. Sulaiman Al Habib Medical Journal)
Opioid-induced respiratory depression (OIRD) is a serious threat that can lead to brain damage and death. Morphine is a commonly used opioid for postoperative pain management. However, the window during which patients are at risk of OIRD, as described in the literature, is largely based on the drug’s pharmacokinetics rather than actual clinical experiences. For morphine, OIRD is generally noted to occur within 5–72 min following administration. In this case, we present the case of a 73-year-old female who underwent open herniorrhaphy and developed respiratory depression 5 h after receiving an intravenous (IV) dose of morphine. The diagnosis of OIRD was confirmed by a positive response to naloxone. Defining a window during which patients are at risk of developing respiratory impairment after opioid administration has significant practical implications for the management of postoperative patients. Based on its half-life and our clinical experience, healthy patients receiving a therapeutic dose of IV morphine may develop OIRD for up to 6 h following administration. During this period, close monitoring is strongly recommended to ensure early detection and intervention if respiratory depression occurs.